A study to Determine the Knowledge on Early Signs of Myocardial Infarction among Adult patients in Medicine OPD at Pondicherry Institute of Medical Sciences, Pondicherry - Tajum Nisha. A; Sunitha kumari; Sureka.S; Suvetha.G; Swetha.T; Thamizharasi.K; Vijiyalakshmi; Vinitha.D; Vinothini.C; R, Rajalakshmi.; R. K. Ravichandran; Malarvizhi. S (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2021)
Myocardial infarction is the leading cause of death in the world. Acute myocardial infarction occurs when the blood supply to heart is interrupted. The most commonly one is due to occlusion of coronary artery following by the rupture of a vulnerable atherosclerotic plaque, which resulting in ischemia and oxygen inadequate. The present study was aimed to determine the knowledge on early signs of Myocardial Infarction among adult patients in Pondicherry Institute of Medical Science. Descriptive study was adopted in this study. Study was conducted among adult patient in medicine OPD, 165 Participants were selected by convenient sampling. The structured knowledge questionnaires were used regarding early signs of myocardial infarction among adult patients. Among 165 participants 44(26.7%) had inadequate knowledge, 80(48.5%) had average knowledge and 41(24.8%) had adequate knowledge. There is association between the knowledge selected socio demographic variables. Adult patients who attended medicine OPD have average knowledge on early signs of myocardial infarction. The current study recommended that they have to be educated about the early signs of myocardial infarction.